2018
DOI: 10.1186/s41601-018-0089-x
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring system for real time detection and classification of transmission line faults in a power grid using PMU measurements

Abstract: Remote monitoring of transmission lines of a power system is significant for improved reliability and stability during fault conditions and protection system breakdowns. This paper proposes a smart backup monitoring system for detecting and classifying the type of transmission line fault occurred in a power grid. In contradiction to conventional methods, transmission line fault occurred at any locality within power grid can be identified and classified using measurements from phasor measurement unit (PMU) at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The PMU usage increased in 2004 when the U.S.-Canada investigation report of the 2003 blackout was released. The blackout report recognized that many of North America's major blackouts have been caused by inadequate situational awareness for grid operators and recommended the use of synchrophasor technology to provide real-time wide-area grid visibility [15], [16]. It was demonstrated that new technology and investment was needed to provide adequate situational awareness and the ability to react to such a major disturbance.…”
Section: Synchrophasor Data Description a Related Work Of Synchmentioning
confidence: 99%
“…The PMU usage increased in 2004 when the U.S.-Canada investigation report of the 2003 blackout was released. The blackout report recognized that many of North America's major blackouts have been caused by inadequate situational awareness for grid operators and recommended the use of synchrophasor technology to provide real-time wide-area grid visibility [15], [16]. It was demonstrated that new technology and investment was needed to provide adequate situational awareness and the ability to react to such a major disturbance.…”
Section: Synchrophasor Data Description a Related Work Of Synchmentioning
confidence: 99%
“…Fault prediction is accomplished by Rajaraman et al using the zero sequence, negative sequence and positive sequence of currents [12]. The frequency coefficients of equivalent power factor angle variation and nominal voltage coefficients are used as inputs to the support vector machine (SVM) classifier for predicting the type of fault in reference [13]. A synchrophasor assisted protection scheme for the protection of a long transmission line compensated with the shunt FACTS device is presented in reference [14].…”
Section: B Related Workmentioning
confidence: 99%
“…SA gives an estimate of the power system operator's ability to perceive and take commensurate control actions. From the power system perspective, SA is defined as the perception of the power system by measuring various parameters, comprehending the data obtained from the components for improved SA, and prognosis of the situation of the system depending on the interpretation of the data captured [3,4].…”
Section: Introductionmentioning
confidence: 99%